1992
DOI: 10.1128/jb.174.11.3695-3706.1992
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Bacillus subtilis transcription factor sigma B by a regulatory pathway responsive to stationary-phase signals

Abstract: Alternative transcription factor sigma B of Bacillus subtilis controls a stationary-phase regulon induced under growth conditions that do not favor sporulation. Little is known about the metabolic signals and protein factors regulating the activity of sigma B. The operon containing the sigma B structural gene has the gene order orfV-orfW-sigB-rsbX, and operon expression is autoregulated positively by sigma B and negatively by the rsbX product (rsbX = regulator of sigma B). To establish the roles of the orfV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
223
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(233 citation statements)
references
References 45 publications
8
223
2
Order By: Relevance
“…This operon is transcribed from a B -dependent promoter and has the gene order rsbV-rsbW-sigB-rsbX (29). Genetic analysis has shown that the RsbW protein is a key negative regulator responsible for rendering B inactive during logarithmic growth (8). Subsequent biochemical analysis has shown that RsbW is an antifactor that binds directly to B and controls its activity by preventing its association with the RNA polymerase core enzyme (3).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This operon is transcribed from a B -dependent promoter and has the gene order rsbV-rsbW-sigB-rsbX (29). Genetic analysis has shown that the RsbW protein is a key negative regulator responsible for rendering B inactive during logarithmic growth (8). Subsequent biochemical analysis has shown that RsbW is an antifactor that binds directly to B and controls its activity by preventing its association with the RNA polymerase core enzyme (3).…”
mentioning
confidence: 99%
“…Significantly, recent work has shown that B is also activated in logarithmically growing cells by a variety of environmental stresses that limit growth, including hyperosmosis, heat, oxidative stress, and ethanol shock (4, 6, 51). These findings have led to the proposal that B controls a general stress regulon (6).Some signals of environmental stress are conveyed to B by a regulatory network encoded by the three genes adjacent to the B structural gene in the sigB operon (2,6,8). This operon is transcribed from a B -dependent promoter and has the gene order rsbV-rsbW-sigB-rsbX (29).…”
mentioning
confidence: 99%
See 3 more Smart Citations